A Case of T-Cell Acute Lymphoblastic Leukemia after Treatment of Acute Promyelocytic Leukemia - Bee, P.C.; Gan, G.G.; Sangkar, J.V.; Teh, A.; Goh, K.Y. (Springer Verlag (Germany), 2004)
We diagnosed T-cell acute lymphoblastic leukemia (T-ALL) with multiple cytogenetic abnormalities in a 17-year-old girl a year after she had received a diagnosis of acute promyelocytic leukemia (APML). After the diagnosis of APML in June 2001, the patient was treated with idarubicin and all-trans-retinoic acid. In September 1999, her younger sister also received a diagnosis of APML and to date has remained well. T-ALL after remission of APML is very rare, and only 1 such case has been reported. Possible causes include therapy-related reasons, genetic susceptibility to leukemia, and environmental exposure.